Lost in transition : removing, resettling, and renewing Appalachia - Purcell, Aaron D., 1972- (Knoxville : The University of Tennessee Press, 2021)
"Volume editor Aaron D. Purcell presents this thematic and chronological exploration of twentieth-century removal and resettlement projects across southern Appalachia. The work's seven case studies, addressing public land removal actions in Virginia, Kentucky, the Carolinas, and Tennessee from the 1930s through the 1960s, reveal confrontations between past and present, federal agencies and citizens, and original accounts and contemporary interpretations. The result is a critical analysis of fact, mythology, and storytelling that illustrates the important role of place in southern Appalachian history"--
The permanent enjoyment of the past / Aaron D. Purcell -- Loss, betrayal, and the power of stories: healing lost communities in the Great Smoky Mountains / Margaret Lynn Brown -- At the bottom of the Loyston Sea: the Tennessee Valley Authority and loss in the Norris Basin / Aaron D. Purcell -- The gift of good land: loss, resettlement, and stewardship through everyday nature in the Shenandoah National Park and on the New River / Katrina M. Powell and Savannah Paige Murray -- Contested sacrifice: loss and the creation of Mammoth Cave National Park / Alyssa D. Warrick -- Layers of loss: removal, segregation, and reconversion at Oak Ridge, Tennessee / Russell Olwell -- When minds wander back: memory and loss on the road to nowhere / Matthew Chisholm -- Any who see the valley would regret its loss forever: the Keowee-Toxaway Project, Duke Power, and loss in northwestern South Carolina / Austin Gregory -- Can you go home again? The meanings of Appalachian identity, displacement, and memory / Stephen Wallace Taylor.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Appalachians (People) -- Relocation -- History -- 20th century; Appalachians (People) -- Relocation -- Case studies; Appalachians (People) -- Ethnic identity; Persons displaced by eminent domain -- Appalachian Region, Southern -- Case studies; Public lands -- Appalachian Region, Southern -- 20th century; Public lands -- Social aspects -- Appalachian Region, Southern; Terres publiques -- Appalaches (Sud) -- 20e siècle.; Terres publiques -- Aspect social -- Appalaches (Sud); Appalachians (People) -- Ethnic identity; Persons displaced by eminent domain; Public lands; Southern Appalachian Region; HISTORY / United States / 20th Century; 1900-1999; Case studies; History